Study on Geological Characteristics of Tight Reservoir and Adaptability of High Efficiency Development Technology - Cao, Weixing (International Journal of Natural Resources and Environmental Studies, 2025)
This paper systematically analyzes the geological characteristics of tight reservoirs, including structural characteristics, sedimentary characteristics, reservoir characteristics, formation pressure and fluid characteristics and temperature field characteristics. The study shows that the distribution of tight reservoirs is significantly influenced by the tectonic environment and sedimentary facies belt, and the reservoirs are characterized by low porosity and permeability, strong heterogeneity and complex pore structure. At the same time, the properties of crude oil are complex and abnormal formation pressure is common. On this basis, this paper constructs a technical system for efficient development of tight reservoirs, covering key technologies such as reservoir evaluation, fracturing reconstruction, displacement technology, numerical simulation and real-time monitoring, and establishes an evaluation index system for technical adaptability from three aspects of reservoir conditions, development effect and economy, and realizes dynamic optimization by coupling multiple methods. In view of the technical bottleneck in the development of tight reservoirs, some improvement directions and suggestions are put forward, such as optimization of reservoir reconstruction technology, improvement of displacement technology, real-time monitoring and dynamic regulation, and optimization of development scheme, in order to provide theoretical basis and technical support for the economic and efficient development of tight reservoirs.